Quantum computing for everyone - Bernhardt, Chris (The MIT Press, 2019)
Quantum computing is a beautiful fusion of quantum physics with computer science. It incorporates some of the most stunning ideas of physics from the twentieth century into an entirely new way of thinking about computation. Quantum Computing is appearing more and more in the news: China teleported a qubit from earth to a satellite; Shor's algorithm has put our current encryption methods at risk; quantum key distribution will make encryption safe again; Grover's algorithm will speed-up data searches. But what does all this really mean? How does it all work? This book explains quantum computing to readers comfortable with high school mathematics. This book is aimed at the general reader. It only requires high school mathematics, but still manages to thoroughly explain most of the standard topics. These include quantum teleportation, superdense coding, error correction and quantum algorithms. This is the first book aimed at this market. Other books that cover the same material assume a higher level of mathematical sophistication. This book simplifies that mathematics as much as possible. It proceeds gently with many examples--